2016
DOI: 10.1038/srep23836
|View full text |Cite
|
Sign up to set email alerts
|

pH Induced Conformational Transitions in the Transforming Growth Factor β-Induced Protein (TGFβIp) Associated Corneal Dystrophy Mutants

Abstract: Most stromal corneal dystrophies are associated with aggregation and deposition of the mutated transforming growth factor-β induced protein (TGFβIp). The 4th_FAS1 domain of TGFβIp harbors ~80% of the mutations that forms amyloidogenic and non-amyloidogenic aggregates. To understand the mechanism of aggregation and the differences between the amyloidogenic and non-amyloidogenic phenotypes, we expressed the 4th_FAS1 domains of TGFβIp carrying the mutations R555W (non-amyloidogenic) and H572R (amyloidogenic) alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…It has been concluded that the rate and efficiency of proteins fibrillation are ruled by the proteins hydrophobic-hydrophilic nature, secondary structure changes, possibility of establishing electrostatic, πˑˑˑπ and hydrogenbonding interactions, among others, which can be potentiated by fibrillation agents [12][13][14][15][16][17][18][19][20][21] . Two major mechanisms of fibrils formation have been proposed: (i) seedling of fibrils in the form of misfolded monomeric intermediates, showing a lag phase in the kinetics curve of fibrils formation 22 ; and (ii) formation of misfolded oligomer intermediates as seeds, in which a lag phase is absent in the kinetics curve 23 . Accordingly, when the goal is to induce proteins fibrillation, fibrillation agents exhibiting both polar and nonpolar domains are the best option since they can induce the formation of misfolded oligomer intermediates, while assisting in fast fibrillation by surpassing the lag phase.…”
mentioning
confidence: 99%
“…It has been concluded that the rate and efficiency of proteins fibrillation are ruled by the proteins hydrophobic-hydrophilic nature, secondary structure changes, possibility of establishing electrostatic, πˑˑˑπ and hydrogenbonding interactions, among others, which can be potentiated by fibrillation agents [12][13][14][15][16][17][18][19][20][21] . Two major mechanisms of fibrils formation have been proposed: (i) seedling of fibrils in the form of misfolded monomeric intermediates, showing a lag phase in the kinetics curve of fibrils formation 22 ; and (ii) formation of misfolded oligomer intermediates as seeds, in which a lag phase is absent in the kinetics curve 23 . Accordingly, when the goal is to induce proteins fibrillation, fibrillation agents exhibiting both polar and nonpolar domains are the best option since they can induce the formation of misfolded oligomer intermediates, while assisting in fast fibrillation by surpassing the lag phase.…”
mentioning
confidence: 99%
“…This region is clinically important as more than 16 different mutations have been reported and many of them alter the overall net charge of the protein, which leads to the formation of amyloid deposits in the cornea. We recently reported a 23-residue peptide from this region (E 611 PVAEPDIMATNGVVHVITNVLQ 633 ) that forms amyloid fibrils under physiological conditions [ 26 , 27 ]. Thus, we synthesized five different peptides from clinically significant mutations for the present study ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutants associated with corneal dystrophies exhibit tissue damage in disease conditions. We have shown previously [ 27 ] that β-oligomeric aggregates of TGFBIp mutants display cytotoxicity in HCSF cells. Analysis of the cytotoxicity of peptides on corneal fibroblasts by label-free xCELLigence in both the amyloidogenic and the prefibrillar forms indicated considerable differences in the inhibition of cell proliferation between the two states, although no cytotoxic effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases of this disease, mutated HsTgfbi forms aggregates in the corneal stroma. This is due to the thermal and pH instability of the protein and to its high abundance in the cornea [ 85 ]; however, the condition might not help us to understand HsTgfbi function. A complete Tgfbi gene knockout in mice caused neither corneal abnormalities nor any other major defects [ 86 ], suggesting compensation by other ECM molecules.…”
Section: Biological Aspects Of Fas1 Domain Proteins Across the Trementioning
confidence: 99%